2021
DOI: 10.1097/mat.0000000000001454
|View full text |Cite
|
Sign up to set email alerts
|

Hemolysis Testing In Vitro: A Review of Challenges and Potential Improvements

Abstract: Many medical devices such as cardiopulmonary bypass systems, mechanical heart valves, or ventricular assist devices are intended to come into contact with blood flow during use. In vitro hemolysis testing can provide valuable information about the hemocompatibility of prototypes and thus help reduce the number of animal experiments required. Such tests play an important role as research and development tools for objective comparisons of prototypes and devices as well as for the extrapolation of their results t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 80 publications
1
7
0
Order By: Relevance
“…The prototype status of the oxygenator may have caused a significant increase in hemolysis, because the entire casing was printed. Recently, Petersdorff-Campen et al [32] showed an increase in hemolysis in printed blood pumps of 620 %, which may explain our results. Last, we have successfully used a mobile gas blender that allows quick, individual, and automatable gas mixtures of medical oxygen and ambient air.…”
Section: In-vitro Evaluationsupporting
confidence: 56%
“…The prototype status of the oxygenator may have caused a significant increase in hemolysis, because the entire casing was printed. Recently, Petersdorff-Campen et al [32] showed an increase in hemolysis in printed blood pumps of 620 %, which may explain our results. Last, we have successfully used a mobile gas blender that allows quick, individual, and automatable gas mixtures of medical oxygen and ambient air.…”
Section: In-vitro Evaluationsupporting
confidence: 56%
“…30 Challenges for the translatability of nanomaterials between in vitro and in vivo applications include issues with stability, activity, and biocompatibility of nanomaterials. 31 The interplay of hemolysis and protein corona formation can contribute to this discrepancy between in vitro and in vivo studies. 32 Mailänder and co-workers compared the protein corona profile between coronas formed in mouse blood and in vivo .…”
Section: In Vivo Translatability Of Nanoparticlesmentioning
confidence: 99%
“…Studies have shown that hemolysis is a major challenge to the preparation of hemocompatible hemostatic materials [ 82 , 83 , 84 , 85 ]. Therefore, the hemocompatibility of a hemostatic material is evaluated by the degree of erythrocyte lysis and hemoglobin dissociation.…”
Section: Hemostatic Mechanism Of Cs Hydrogelsmentioning
confidence: 99%